INTERNALISASI NILAI DISIPLIN SISWA MELALUI PROGRAM BARIS-BERBARIS DI SEKOLAH DASAR - Maharani, Andini Putri; Ummah, Fiena Saadatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the marching habit program and analyze its impact on student discipline at Khadijah Elementary School in Wonorejo, Surabaya. This study uses a qualitative approach with a case study. Data collection was conducted through observation, interviews, and documentation involving class teachers, the vice principal for student affairs, and lower grade students. The results show that the marching habit program is implemented routinely in the morning and during activity transitions. The implementation of this program has a positive impact on aspects of time discipline, attitude, and student compliance. Students showed an increase in orderliness, ability to follow instructions, and responsibility. Thus, the marching habit has proven to be an effective strategy in fostering discipline in elementary school students.